GEMBALA SIDANG MENJADI ORANGTUA BAGI JEMAATNYA DALAM MENGHADAPI KRISIS KARAKTER AKHIR ZAMAN - Damayanti Nababan; Friskila Sitanggang; Ezra limbong; Seventina novita; Zainal Sihombing (Publisher STPKat, 2022)
One of the problems in pastoral care is not understanding the spiritual needs and character of each congregation. A pastor acts as a parent and teacher for his congregation. In the process, a pastor of the congregation often does not reach the ultimate goal of his pastoral care, namely the maturity of the faith of his congregation with a sign of changing earthly characteristics into heavenly ones. This is because there is no brotherly love and the pastor does not fully understand the spirit of heresy that develops in the congregation and how to avoid this error that starts in the church. In line with this problem, this article seeks to provide ideas and explanations about the role of the pastor as a parent for his congregation in facing the end-time character crisis. The research method used in this paper is a qualitative study with a literature analysis approach.